2023
DOI: 10.1126/sciadv.adf6205
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of protein condensates to ordered lipid domains determines functional membrane organization

Abstract: During T cell activation, the transmembrane adaptor protein LAT (linker for activation of T cells) forms biomolecular condensates with Grb2 and Sos1, facilitating signaling. LAT has also been associated with cholesterol-rich condensed lipid domains; However, the potential coupling between protein condensation and lipid phase separation and its role in organizing T cell signaling were unknown. Here, we report that LAT/Grb2/Sos1 condensates reconstituted on model membranes can induce and template lipid domains, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…We use the term phase coupling to denote this phenomenon. Recent work suggests that similar protein-lipid phase coupling occurs at the plasma membrane and plays an important role in T-cell activation, suggesting a broader role such mechanisms across cellular systems (Chung et al, 2021; Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We use the term phase coupling to denote this phenomenon. Recent work suggests that similar protein-lipid phase coupling occurs at the plasma membrane and plays an important role in T-cell activation, suggesting a broader role such mechanisms across cellular systems (Chung et al, 2021; Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical studies have suggested such a phenomenon might occur (Andes-Koback and Keating, 2011; Nesterov et al, 2021; Rouches et al, 2021). However, direct evidence for such phase coupling has been restricted to interactions between condensates and the plasma membrane (Chung et al, 2021; Lee et al, 2019; Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, membranes have been reported to control the size of intracellular condensates and modify their material properties 14 . Furthermore, the crosstalk between membranes and condensates can promote phase separation coupling in the lipid and the protein phases 15,16,17 also shown in cytoplasm mimetic systems 18 . While the field of membrane-condensate interactions is rapidly gaining momentum, important cues are still missing in our understanding of the underlying mechanisms associated with the resulting structural changes and remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…15 BCs at the cell membrane have been recently shown to function in actin assembly 16 and in a Ras signaling pathway. 17 Evidence of membrane remodeling by BCs has been provided for the N-terminal low-complexity domain of fused in sarcoma (FUS LC), 18 for endocytic coat proteins with intrinsically disordered prion-like domains, 19,20 for transmembrane adaptor Linker of Activation of T-cells (LAT) during T-cell activation, 21 for lipid vesicles within a synapsin-rich liquid phase, 22 and for TIS granules interacting with the endoplasmic reticulum. 23 Such membrane reorganization processes mediated by BCs are anticipated to be a consequence of capillary forces generated at the membrane-condensate interface.…”
Section: Introductionmentioning
confidence: 99%